2020
DOI: 10.1016/j.biocon.2019.108351
|View full text |Cite
|
Sign up to set email alerts
|

Conservation value of tropical forests: Distance to human settlements matters more than management in Central Africa

Abstract: Tropical forests in Central Africa host unique biodiversity threatened by human degradation of habitats and defaunation. Forests allocated to conservation, production and community management are expected to have different conservation values. Here, we aimed to identify the determinants of the conservation value of tropical forests in southeastern Cameroon, by disentangling the effects of forest allocations, proximity to human settlements, and local habitat. We inventoried two taxonomical groups: mammal specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 87 publications
5
44
0
Order By: Relevance
“…Spatial avoidance of human‐dominated habitats by carnivores has been frequently reported (Dias et al , 2019; Heim et al , 2019; Lhoest et al , 2020), and may be explained by fear of humans (Frid & Dill, 2002; Miller & Schmitz, 2019; Suraci et al , 2019). Humans have presumed the role of ‘super predator’ in wildlife communities globally (Darimont et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial avoidance of human‐dominated habitats by carnivores has been frequently reported (Dias et al , 2019; Heim et al , 2019; Lhoest et al , 2020), and may be explained by fear of humans (Frid & Dill, 2002; Miller & Schmitz, 2019; Suraci et al , 2019). Humans have presumed the role of ‘super predator’ in wildlife communities globally (Darimont et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Body size is a key aspect in predator–prey interactions; large‐sized animals may have a higher perception of the risk of predation than smaller‐sized ones (Davidson et al, 2009; McGraw & Zuberbuhler, 2008; Preisser & Orrock, 2012; Zuberbühler, 2007). Evidence of the effects of body size on the response of mammal species to human disturbance was recently reported in south‐east Cameroon (Lhoest et al, 2019) and Gabon (Beirne et al, 2019), where there was a gradient of increasing body mass of mammals with increasing distance to villages. The effects of body size on the response of different species to predation risk is related to the fact that different species present different flight initiation distances, and the flight initiation distance increases as body size increases (Gotanda, Turgeon, & Kramer, 2009; Møller & Erritzøe, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The avoidance of human settlements or presence is often attributed to hunting; under such circumstances, animal species may find refuge where hunting intensity is low (Blom et al, 2005; Vanthomme et al, 2013). Although we did not measure hunting pressure in our analyses, the distance to human settlements was considered as a proxy for hunting pressure because the increasing distance to villages is likely to correspond to a decrease in hunting signs (Beirne et al, 2019; Koerner et al, 2017; Lhoest et al, 2019). Previous studies in our research site have shown that hunting signs, and not research activities, determined space use by gorillas and chimpanzees for nesting along transects (Tagg et al, 2018; Tagg & Willie, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also below the sustainability standard of the maximum production of wild meat roughly estimated between 150 and 200 kg/km 2 /year in tropical forests [76]. Even if bushmeat consumption in Eschiambor could then seem to be sustainable, inventories of mammal populations have shown that only small animals remain in these areas close to villages and roads due to past hunting pressure [87]. Indeed, a high and growing hunting pressure induces a decline in the biomass of forest vertebrates, with large-bodied preferred game species declining rapidly [88,89].…”
Section: Bushmeat Consumptionmentioning
confidence: 99%